Biomechanical study of stress-strain states of the system «endoprosthesis humerus» in terms of tumor resection - Vyrva, Oleg; Mikhanovsky, Dmytro; Karpinsky, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To compare the stress-strain state of the «prosthesis – humerus» system with loading on tension, bending and torsion in the case of resection in the upper, middle and lower thirds of the humeral diaphysis. Methods: It was developed a mathematical model that simulated cases of defects in the upper third, half and 2/3 of the proximal humerus formed after resection of the tumor and substituted with endoprosthesis. We investigated two types of implants: the first was fixed exclusively by intramedullary stem, the second had a combined mounting system and was fixed not only with the help of intramedullary stem but with the help of extracortical plates attached to the body of the endoprostesis and fixedly embraced the distal humerus. We tested models with three types of loadins — tension, bending and torsion. Results: Having examined the first type of endoprosthesis we found that under tensile loading maximal stresses occur in the distal part of the bone at the level of the end of the intramedullary stem, and the most favorable situation is the resection of the humerus at the level of the upper third. Research on flexing showed that the maximal loading concentrates in the central part of the model and does not depend on the level of resection of the humerus. The worst option was resection of the upper half of the humerus due to the critical area of maximum stress occurring in the basis of endoprosthesis at the junction of the body of the implant into the bone. The study of the second type of endoprosthesis revealed that for all kinds of loading additional extracortical plates give an opportunity to reduce the level of stresses in the bone tissue as well as the loading onto the critical zone. This combined system of fixing of the endoprosthesis will allow to significantly reduce the amount of complications associated with the implant and the bone in the early and late postoperative period.